Buy Now Pay Later Impact to Online Food Delivery Transactions of University Student Customer Segment - Iqbal Anugrah Alhadi Parinduri; G. N. Sandhy Widyasthana; Mustika Sufiati (Publikasi Indonesia, 2025)
This study investigates the impact of Buy Now Pay Later (BNPL) adoption, specifically XYZLater, on online food delivery (OFD) transactions among university students. Despite high usage of OFD services driven by convenience and promotions, BNPL adoption for small, routine purchases like food delivery remains limited due to perceptions of BNPL as a debt-related feature intended for large, infrequent expenses. This study aims to understand the behavioral impact of BNPL on transaction frequency, order value, and customer retention within the university student segment. Employing a mixed-method approach, the research combines quantitative analysis of historical transaction data and surveys with qualitative interviews to explore students' perceptions and financial behaviors. Results reveal that while students trust digital payment ecosystems and frequently use OFD platforms, hesitation to use BNPL for daily needs persists, driven by fears of overspending and financial mismanagement. However, reframing BNPL as a smart financial assistant rather than a credit facility emerges as a promising strategy to increase adoption, transaction volume, and loyalty. The study suggests that targeted marketing, financial literacy initiatives, and user control features could enhance BNPL's alignment with student behaviors. These findings offer actionable insights for OFD platforms seeking sustainable growth in competitive markets by leveraging BNPL to address price sensitivity and budgeting needs of young consumers.